Design and synthesis of a novel ZB716-d6 as a stable isotopically labeled internal standard. Issue 11 (18th June 2022) - Zheng, Shilong; Liu, Jiawang; Kang, Borui; Wang, Guangdi
Abstract: ZB716 is a synthetic, steroidal, orally active anti-estrogen agent that is under clinical development for the treatment of estrogen receptor (ER)-positive metastatic breast cancer. The stable isotope-labeled ZB716 was required for use as an internal standard in LC-MS/MS assays. Therefore, a novel deuterated ZB716 (ZB716-d6) as an isotopically labeled internal standard was designed and synthesized through a newly developed route, which prepared ZB716-d6 in eight steps from the commercially available deuterium-labeled starting material [ 2 H6 ]pentafluoropentanol. This procedure is very practicable and gives the final compound in good yield (19% total yield) and high purity (D, >99%, chemical purity 98%). At present, ZB716-d6 has been successfully used as an internal standard in clinical bioanalysis. Graphical Abstract: UF0001